Pengaruh Variasi Arus Dan Jenis Elektroda RB-26 Terhadap Kekuatan Tarik Sambungan Las SMAW Pada Baja AISI 1060 - Husaini, Muhammad Alwi (CV. IRA PUBLISHING, 2025)
This research was conducted to analyse the effect of welding current variation and electrode type on the tensile strength of SMAW welds on AISI 1060 high-carbon steel. Quantitative experimental methods were applied in the laboratories of the Medan State Polytechnic and the Al-Azhar University in Medan. AISI 1060 steel with a thickness of 8 mm and a carbon content of 0.60-0.70% was welded using RB-26 electrodes with current variations of 80A, 90A, and 100A. Tensile testing was conducted in accordance with ASTM E8/E8M to measure ultimate tensile strength (UTS), yield strength, and specimen elongation. The research results show that the best mechanical performance was obtained at a welding current of 100A with a UTS of 338.58 N/mm², a yield strength of 117.77 N/mm², and an elongation of 5.42%. Conversely, the lowest UTS of 123.4 N/mm² and elongation of 4.47% were produced at a current of 80A due to insufficient heat input. Increased tensile strength was found to be proportional to increasing welding current up to an optimal limit, but excessive current can cause detrimental microstructural changes. It is concluded that selecting appropriate welding current parameters is crucial for obtaining high-quality weld joints on AISI 1060 steel, with a current of 100A recommended as optimal.